Glass-free Li2SiO3-LiF ceramics with high thermal conductivity. (December 2022) - Wang, Mingxia; Zhong, Chaowei; Li, Enzhu; Yi, Yong; Liu, Jingsong; Zhang, Shuren
Abstract: In the past few decades, Low temperature co-fired ceramics (LTCC) technology with high thermal conductivity had been developed to meet the requirements of high-density integrated devices packaging. This work investigates the effect of LiF sintering agent on the densification, microstructure and thermal conductivity of LTCC material (Li2 SiO3 +4 wt% Al2 O3 -x wt% LiF (x = 1, 2, 3, 4)). The enhanced densification and a high thermal conductivity value of 11.36 W/mK are achieved when adding 2 wt% LiF and sintered at 940 ℃. Besides, the phonon-dispersion relation of Li2 SiO3 lattice indicates that the anharmonicity interaction between low-frequency phonons are the primary factor in reducing the thermal conductivity of material. Furthermore, the Raman spectra were used to analyze the phonon scattering mechanism of all samples. The addition of the LiF changes the full width at half maximum (FWHM) which is inversely proportional to the phonon mean free path. And the reduced FWHM of Raman spectra implies higher thermal conductivity of ceramics. Base on the above results, the novel glass-free high thermal conductivity and low sintering temperature Li2 SiO3 + 4 wt% Al2 O3 -2 wt% LiF ceramic was prepared successfully with great potential in high heat conduction LTCC materials. This work could bring new insights for exploring novel high thermal conductivity ceramic materials. Graphical Abstract: ga1